2020
DOI: 10.3390/genes11050510
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Evolutionary Patterns, and Expression Analysis of bZIP Gene Family in Olive (Olea europaea L.)

Abstract: Olive (Olea europaea.L) is an economically important oleaginous crop and its fruit cold-pressed oil is used for edible oil all over the world. The basic region-leucine zipper (bZIP) family is one of the largest transcription factors families among eukaryotic organisms; its members play vital roles in environmental signaling, stress response, plant growth, seed maturation, and fruit development. However, a comprehensive report on the bZIP gene family in olive is lacking. In this study, 103 OebZIP genes from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Although the functions of most of the motif elements were unknown, certain motifs were observed in specific bZIP members, suggesting that these transcription factors had specific functions. A similar finding has been reported in other species, indicating that some elements are relatively conserved evolutionarily [ 27 ]. These unknown elements may have specific functions in each subfamily, which may provide a new reference for the functional divergence among members of each subfamily.…”
Section: Results and Analysissupporting
confidence: 88%
“…Although the functions of most of the motif elements were unknown, certain motifs were observed in specific bZIP members, suggesting that these transcription factors had specific functions. A similar finding has been reported in other species, indicating that some elements are relatively conserved evolutionarily [ 27 ]. These unknown elements may have specific functions in each subfamily, which may provide a new reference for the functional divergence among members of each subfamily.…”
Section: Results and Analysissupporting
confidence: 88%
“…Therefore, the genetic information of G. biloba is of great research value in plant growth and development, pest and disease defense, abiotic stress, and tree evolution. To date, the bZIP gene family has been identified in A. thaliana (78 bZIPs) 30 , Populus (86 bZIPs) 37 , Raphanus sativus (135 bZIPs) 15 , Solanum tuberosum (80 bZIPs) 38 , Brassica napus (247 bZIPs) 38 , and Olea europaea (103 bZIPs) 39 . However, the bZIP transcription factors in G. biloba have not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that MYB and bZIP transcription factors participated in regulating the synthesis of FAs ( Yamamoto et al, 2009 ; Rong et al, 2020 ), and MYB played important roles in VLCFA biosynthesis particularly ( Raffaele et al, 2008 ). A weighted gene co-expression network analysis in Acer truncatum Bunge ( A. truncatum ) showed that MYB and bZIP transcription factors were involved in regulating NA biosynthesis ( Ma et al, 2020 ).…”
Section: Na Biosynthesis and Assemblymentioning
confidence: 99%